The Development of Indonesia's Fintech and Comparation with India in Terms of Complex Interdependence Theory and Digital Economy - Iswardhana, Muhammad Ridha (SAINTIS Publishing, 2024)
Economic issues has become one of the world's major problems, along with the economic crisis and distrust of banks. Not only in developed countries, but also in various developing countries of the world, such as Indonesia and India. Both countries are equally as developing countries with high numbers of people and informal workers, that have great opportunities in the digital economy. The research found that although India is the tech hub of Asia, while Indonesia can combine technology with the local economy through fintech programs. The existence of Fintech Indonesia is as much about increasing the use of technology as it is about bridging the challenges of the micro-economy. Reflected both in the Indonesian and Indian economies that seek not only to rely on commodities and natural resources but tried to move on to technology and the digital-based economy. At the same time also appears Fintech phenomenon is growing rapidly. The author will use qualitative descriptive methodology and the concept of digital economy also the complex interdependence theory. This research has aims to answer about opportunities and development of fintech in Indonesia compared to India. This study was chosen because of the need for the digital economy and the bigger hope of Fintech in the Indonesian economy, referring that happening in India.